Результаты экспериментальных исследований метода иерархическо-координационного управления сетевыми ресурсами в ТКС - Симоненко, Д. В.; Беленков, А. Г. (ХНУРЭ, 2009)
At the decision of problems on management of network resources in TCS very sharply there is a problem of increase of scalability of received decisions. In work results of experimental researches which are connected with an estimation of scalability of decisions of problems of management of network resources TCS at maintenance of the guaranteed quality of service are offered.